Penatalaksanaan Holistik Pasien Perempuan Dewasa Usia 54 Tahun Dengan Dermatitis Kontak Alergi Melalui Pendekatan Kedokteran Keluarga - Dzakirah, Inas; Karyus, Aila (CV. Jasa Sukses Abadi, 2024)
Allergic contact dermatitis is dermatitis that occurs due to exposure to allergens outside the body, mediated by a type 4 hypersensitivity reaction. This disease is generally synonymous with pruritus has erythema, oedem,. This disease results in a high rate of morbidity and its prevalence has increased in recent decades. This article is a form of application of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and management based on a problem-solving framework with a patient-centered and family-centered approach. This study is a Case Report. Primary data were obtained through autoanamnesis, physical examination, home visits to complete family and psychosocial data, as well as the environment. Assessment based on a holistic diagnosis from the beginning, process and end of the study quantitatively and qualitatively.Adult female patient aged 54 years with allergic contact dermatitis. On internal factors in cases such as genetic factors, age factors, and ignorance of the originator. External factors are the lack of family knowledge about kontak alergic dermatitis, its complications and the environment that has many allergens. Pharmacological and non-pharmacological interventions were carried out in the form of education in preventing the onset of symptoms of allergic contact dermatitis in patients. Diagnosis and management of these patients has been carried out in a holistic, patient-centered, family approach and based on several theories and recent research. In the process of change, patients and families have reached the adoption stage.